Advanced interconnects for ULSI technology - Baklanov, Mikhail; Ho, P. S.; Zschech, Ehrenfried (Hoboken, NJ : Wiley, 2012)
"This book presents an in-depth overview of present status, novel developments and new materials and approaches for advanced interconnect technology"--
Front Matter -- Colour Plates -- Section I: Low-. Low- Materials: Recent Advances / Geraud Dubois, Willi Volksen -- Ultra-Low- by CVD: Deposition and Curing / Vincent Jousseaume, Aziz Zenasni, Olivier Gourhant, Laurent Favennec, Mikhail R Baklanov -- Plasma Processing of Low- Dielectrics / Hualiang Shi, Denis Shamiryan, Jean-Fraṅois de Marneffe, Huai Huang, Paul S Ho, Mikhail R Baklanov -- Wet Clean Applications in Porous Low- Patterning Processes / Quoc Toan Le, Guy Vereecke, Herbert Struyf, Els Kesters, Mikhail R Baklanov -- Section II: Conductive Layers and Barriers. Copper Electroplating for On-Chip Metallization / Valery M Dubin -- Diffusion Barriers / Michael Hecker, Rene Hubner -- Section III: Integration and Reliability. Process Integration of Interconnects / Sridhar Balakrishnan, Ruth Brain, Larry Zhao -- Chemical Mechanical Planarization for CuLow- Integration / Gautam Banerjee -- Scaling and Microstructure Effects on Electromigration Reliability for Cu Interconnects / Chao-Kun Hu, Rene Hubner, Lijuan Zhang, Meike Hauschildt, Paul S Ho -- Mechanical Reliability of Low- Dielectrics / Kris Vanstreels, Han Li, Joost J Vlassak -- Electrical Breakdown in Advanced Interconnect Dielectrics / Ennis T Ogawa, Oliver Aubel -- Section IV: New Approaches. 3D Interconnect Technology / John U Knickerbocker, Lay Wai Kong, Sven Niese, Alain Diebold, Ehrenfried Zschech -- Carbon Nanotubes for Interconnects / Mizuhisa Nihei, Motonobu Sato, Akio Kawabata, Shintaro Sato, Yuji Awano -- Optical Interconnects / Wim Bogaerts -- Wireless Interchip Interconnects / Takamaro Kikkawa -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Interconnects (Integrated circuit technology); Integrated circuits -- Ultra large scale integration; Integrated circuits -- Ultra large scale integration; Interconnects (Integrated circuit technology); TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- VLSI & ULSI; COMPUTERS -- Logic Design; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- Logic; Integrated circuits -- Ultra large scale integration; Interconnects (Integrated circuit technology); Electronic books